Major advances in amyotrophic lateral sclerosis in 2020 - Divyani Garg; Achal Kumar Srivastava (Apollo Medicine)
Research in amyotrophic lateral sclerosis (ALS), a neurodegenerative condition, has seen advancement in several key areas of research in 2020. These include a thrust to move the classification of ALS from a neuromuscular condition to a neurodegenerative condition, due to research suggesting involvement of cortical areas, and early cortical hyperexcitability. A new criterion for ALS, called the Gold Coast criterion, has been described. The Gold Coast criteria have removed the categories of possible, probable, and definite ALS, to make the diagnosis of ALS more inclusive and permit enhanced eligibility of patients in clinical trials for ALS. New biomarkers, both imaging and protein based, have been described. Advances in therapy have also occurred, with a large phase II clinical trial reporting benefits with sodium phenylbutyrate-taurursodiol.